The Influence of Code Switching and Code-Mixing in the Teaching of Speaking Skills among Students at Al-Husainy Islamic Boarding School, Bima: An Ethnography of Communication Study - Marlina, Leny; Taufiqurrochman, R.; Ifawati, Nur Ila (Abjadia : International Journal of Education, 2025)
This study aims to: (1) describe the forms of code-switching and code-mixing in the teaching of Mahārah Kalām (speaking skills) among students using an ethnography of communication approach; (2) determine the influence of code-switching and code-mixing on the learning of Mahārah Kalām through this approach; and (3) examine the role of code-switching and code-mixing within the ethnographic study of communication at Al-Husainy Islamic Boarding School, Bima City. This is a field research study employing an ethnography of communication approach, conducted at Al-Husainy Islamic Boarding School in Bima City, with twelfth-grade students as research subjects. The data analysis techniques used in this study consist of four stages: reading, data reduction, data presentation, data analysis procedures, and drawing conclusions. The findings show that: (1) the forms of code-switching and code-mixing observed include interlingual code-switching, inter-dialectal code-switching, and switching between Arabic and Indonesian terms. Meanwhile, the types of code-mixing identified include intra-sentential mixing, inter-sentential mixing, peripheral mixing, and dialectal mixing. (2) The influence of code-switching and code-mixing in Mahārah Kalām instruction includes both positive and negative effects. (3) The application of code-switching and code-mixing in the ethnography of communication context contributes to improving students’ adaptability, developing contextual speaking abilities, and enhancing understanding of social roles in communication.